Analisis Tindak Tutur Lokusi, Ilokusi, dan Perlokusi Dalam Wacana Iklan Produk Kecantikan Di Instagram - Anesih Tri Afriyanti; Prasetyo Yuli Kurniawan; Hany Uswatun Nisa (Peneliti.net, 2022)
This study aims to find out (1) to find out the locution speech acts in the beauty product advertising discourse on Instagram, (2) ) to find out the Illocutionary speech acts in the beauty product advertising discourse on Instagram, (3) ) to find out the Perlocution speech acts in the beauty product advertising discourse on Instagram. This research uses a descriptive qualitative approach with pragmatic methods. This research is used to describe and explain the form of locution, illocutionary and perlocutionary speech acts in the discourse of advertisements for products of woe on Instagram. This research has discussed the subject matter regarding locution, illocutionary, and perlocutionary speech acts in the discourse of beauty product advertisements on Instagram. here are 3 things that can be concluded. The results of the ananalysis of speech acts there are 20 data on the form of speech acts in the discourse ofantikan product advertisements on Instagram which were taken from posts in July 2021 to posts in July 2022. There are 20 data analysis results, namely 5 locution speech act data, 10 illocutionary speech act data, and 5 perlocution speech act data.